2-Chloro-5-nitropyridin-4-amine - He, Jian-Ling (International Union of Crystallography, 2012)
The title molecule, C(5)H(4)ClN(3)O(2), possesses mirror symmetry, with all of the atoms lying in the mirror plane. There is an intramolecular N—H⋯O hydrogen bond involving the adjacent –NO(2) and –NH(2) groups. A short C—H⋯O interaction is also observed. In the crystal, adjacent molecules are linked via N—H⋯Cl and N—H⋯N hydrogen bonds, forming chains propagating along [100].